1985
DOI: 10.1055/s-2008-1052537
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline Affects Sleep-Wake State Development in Premature Infants*

Abstract: This study investigated the prolonged effects on state behavior of theophylline administered to infants for apnea of prematurity. There were three groups: Four premature infants who had received theophylline in the preterm period, five premature infants who had not received theophylline, and twenty-eight normal fullterm infants. The Theophylline infants had been off the drug for at least one month prior to the beginning of the study. Sleep-wake states were observed in the home for seven-hour periods when all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 6 publications
4
17
1
Order By: Relevance
“…These findings are again in line with those on piglets, where doxapram had less effect on sleep structure than, for example, theophylline [21]. The latter substance inhibits active sleep also in human neonates [23]. Jitteriness and seizures, side effects reported by other investigators at doses of 2-2.5 mg/kg/h and another indicator that doxapram has an effect on the central nervous system [20], were not observed in our study, possibly because we used slightly lower doses.…”
Section: Discussionsupporting
confidence: 79%
“…These findings are again in line with those on piglets, where doxapram had less effect on sleep structure than, for example, theophylline [21]. The latter substance inhibits active sleep also in human neonates [23]. Jitteriness and seizures, side effects reported by other investigators at doses of 2-2.5 mg/kg/h and another indicator that doxapram has an effect on the central nervous system [20], were not observed in our study, possibly because we used slightly lower doses.…”
Section: Discussionsupporting
confidence: 79%
“…12,24 The potential long-term effects of neonatal methylxanthine treatment on CNS processes controlling sleep and arousal organization require further study.…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal rabbits, one dose (10 mg kg À1 ) of theophylline on postnatal day 1 led to 3 weeks of increased waking, decreased active sleep and delay of quiet sleep development. 26 Similarly, Thoman et al 12 reported that infants previously treated with theophylline, but not currently treated, showed higher rates of wake and drowse/transitional states when examined in the home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theophylline infants had decreased AS as well as alterations in state organization. 132 Nonsteroidal anti-inflammatory agents such as indomethacin and ibuprofen disrupt the sleep cycle, possibly due to the inhibition of prostaglandin synthetase. 133,134 Newborn exposure to alcohol through breast milk caused a general decrease in sleep time and a marked decrease in AS.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%